Investigating Pre-and Post-Seismic TEC Anomalies Related to Moderate Earthquakes in Turkiye - Muhammad, Ahmad; Kulahci, Fatih; Varol, Asaf; Danbatta, Salim Jibrin (Institute of Electrical and Electronics Engineers Inc., 2023)
GPS Total Electron Content (GPS TEC), variations are analyzed over Turkiye for the periods from the 17th of August 2008 to the 21st of September 2008. This analysis was conducted in quite solar and geomagnetic conditions. The standard deviation and seasonal decomposition methods are adapted to study the TEC time series anomalies. For the two major earthquake events with magnitudes 4.7 and 5.1, spatial TEC disturbances are visualized by plotting contoured TEC maps. Shallow earthquakes are considered with a magnitude range. Anomaly detection results suggest the significance of moderate earthquakes in seismic-ionospheric studies. © 2023 IEEE.
4th International Informatics and Software Engineering Conference, IISEC 2023 -- 21 December 2023 through 22 December 2023 -- Ankara -- 196814
Keywords: Ionosphere; moderate earthquakes; Total electron content